Cerkvenoslovanska ostalina na Slovenskem - zgodbe, kraji in osebnosti ljubljanskega dela Supraseljskega zbornika - Babič, Vanda (Slavistična revija, 2011)
The author concentrates on a presentation of the content of the Ljubljana portion of the Codex Suprasiensis, the longest Old Church Slavic Cyrillic manuscript of the tenth-eleventh centuries. In Kopitar's archives, which are now in the Manuscript Collection of the National and University Library in Ljubljana, catalogued under Cod. Kop. 2, it contains 118 preserved folia of a menology, the liturgical readings for the month of March. The first part of the Codex consists of nineteen texts of which seventeen are orthodox hagiographies, one an encomium, and one a prayer. The article gives a detailed presentation of the first ten texts.
Keywords: 10./11. st.; cirilski spomeniki; Codex Suprasliensis; cyrillic manuscripts; hagiografije; menologij; menology; Old Church Slavic language; ortodox hagiography; pravoslavje; pridige; Retko's Codex; Retkov zbornik; rokopisi; sermon; sermons of John Crysostom; stara cerkvena slovanščina; Supraseljski zbornik